2005
DOI: 10.1063/1.1905807
|View full text |Cite
|
Sign up to set email alerts
|

Optical properties of GaN quantum dots grown on nonpolar (11-20) SiC by molecular-beam epitaxy

Abstract: We report on nonpolar GaN quantum dots embedded in AlN, grown on (11-20) 6H–SiC by plasma-assisted molecular-beam epitaxy. These dots are aligned in the growth plane and present a constant aspect ratio of 10. Their optical properties were studied as a function of GaN coverage. Especially, the variation of their emission energy as compared to that of (0001) GaN quantum dots is a clear fingerprint of the reduced internal electric field present in these nonpolar nanostructures. Time-resolved spectroscopy confirme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
54
2

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 64 publications
(58 citation statements)
references
References 18 publications
2
54
2
Order By: Relevance
“…Nevertheless, experimental results indicate increased recombination rates in nonpolar nitride QDs in comparison to polar QDs. 3 Recent theoretical studies have investigated the influence of intrinsic fields on the single-particle states concerning the sign of piezoelectric constants, 4 geometry, 5 and concentration. 6 These studies revealed only a marginal spatial overlap of the electron and hole single-particle ground state in nonpolar QDs implying a very slow recombination due to dipole transitions between the ground states.…”
mentioning
confidence: 99%
“…Nevertheless, experimental results indicate increased recombination rates in nonpolar nitride QDs in comparison to polar QDs. 3 Recent theoretical studies have investigated the influence of intrinsic fields on the single-particle states concerning the sign of piezoelectric constants, 4 geometry, 5 and concentration. 6 These studies revealed only a marginal spatial overlap of the electron and hole single-particle ground state in nonpolar QDs implying a very slow recombination due to dipole transitions between the ground states.…”
mentioning
confidence: 99%
“…Confining the carriers in dislocation-free quantum dots (QDs) or nanowires (NWs) is a possible approach to overcome the impact of structural defects on the radiative recombination yield. The first growth of a-plane GaN/AlN QD structure was demonstrated by the Grenoble research group in 2005 [49]. The emission-energy behavior in these structures as compared to that of the (0001) GaN QDs was a clear fingerprint for a reduced internal electric field present in the nonpolar nanostructures.…”
Section: The First Nonpolar Low-dimensional Nitridebased Structuresmentioning
confidence: 96%
“…A detailed description of the growth process can be found in Refs. [7,8]. Atomic force microscopy performed on the upper uncapped dot layer of similar samples revealed a density of dots of 1.2 × 10 11 cm -2 for sample A and 0.6 × 10 11 cm -2 for sample B.…”
Section: Samples and Experimentsmentioning
confidence: 98%